Potent Antioxidant Activity of Renggak (Amomum dealbatum Roxb.) Fruit and Its Antibacterial Effect Against Klebsiella pneumoniae - Mustariani, Baiq Ayu Aprilia; Dewi, Yuli Kusuma; Raohani; Sulistiyana (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study investigates the antioxidant and antibacterial activities of ethanolic extracts of renggak fruit (Amomum dealbatum Roxb.), an edible plant traditionally consumed in Lombok, Indonesia. The novelty of this research lies in the evaluation of fruit extracts of A. dealbatum, which have been rarely studied compared to other plant parts, particularly in relation to antioxidant potency and antibacterial activity against Klebsiella pneumoniae, a clinically relevant pathogen associated with severe pneumonia and antibiotic resistance. Extraction was carried out using a maceration method with 96% ethanol under controlled temperature and duration to preserve thermolabile compounds. Phytochemical screening revealed the presence of flavonoids, tannins, and terpenoids. Antioxidant activity was evaluated using the DPPH radical scavenging assay, yielding an IC₅₀ value of 10.33 ppm, indicating very strong antioxidant activity compared to other reported Amomum species. Antibacterial activity was assessed using the agar well diffusion method at extract concentrations of 20–100%, showing moderate inhibitory effects against K. pneumoniae with inhibition zones ranging from 7.34 to 9.48 mm. These findings highlight renggak fruit as a promising natural source of antioxidant and antibacterial agents, supporting their potential application as functional food ingredients or natural therapeutics.